Nurses’ knowledge of geriatric problems - Rogala, Justyna; Kozak-Szkopek, Elżbieta (Nursing Problems / Problemy Pielęgniarstwa, 2012)
Introduction. Nurses should have knowledge of geriatric problems needed to plan and carry out nursing care for older patients. Aim of the study. The aim of the study was to assess the level of knowledge about geriatric problems among nurses. We analyzed whether the level of knowledge of nurses depended on place of work, level of education, duration of employment. Material and methods. The study included 60 nurses: 20 employees of residential medical care facility (ZPO), 20 — emergency department (OPD), 20 nursing students (SP). The study was conducted using a questionnaire containing 20 items. Results and conclusions. Correct answers to all questions were given by 63% of the nurses of the ZPO and 60% of the OPD; over 56% of SP answered incorrectly(p < 0.05). Professionally active nurses showed statistically significantly greater knowledge of geriatric problems in comparison with the nursing students. Knowledge of nurses was not significantly higher in the group with higher education and did not depend on the duration of employment. Professional experience of nurses in the care of the elderly had a significant impact on the knowledge of geriatric problems. There is a need for high level of undergraduate education in geriatrics and geriatric nursing and regular postgraduate education of nurses in the field of geriatric care.